1360. Variation in Duration of Antibiotic Therapy for Central-line Associated Blood Stream Infections Caused by Gram Negative Bacilli in Hospitalized Children. (31st December 2020) - Whitmer, Grant R; Scardina, Tonya; Sun, Shan; Zheng, Xiaotian; Patel, Sameer
Abstract: Background: Central-line associated bloodstream infections (CLABSIs) are associated with increased morbidity, mortality, and duration of hospitalization in children. Existing guidelines recommend a broad range (7-14 days) for duration of antibiotic therapy. Unnecessarily prolonged therapy may be associated with emergence of antibiotic resistance and adverse events. Methods: We performed a retrospective review of all patients diagnosed with CLABSIs caused by Gram negative bacilli (GNB) at our institution from August 2009 to April 2019. CLABSI was defined as isolation of a GNB from the blood >48 hours after hospital admission with presence of a central venous catheter. Children who died before completion of treatment were excluded. Data collection variables included severe neutropenia (defined as absolute neutrophil count < 500), immunocompromised status (defined as receipt of bone marrow transplant, solid organ transplant, or immunosuppressive medication), and catheter removal. The duration of effective antibiotic therapy was calculated from the date of last positive culture to discontinuation. Effective therapy was defined as use of an agent to which the isolated organism was susceptible by antimicrobial susceptibility testing. The primary outcome was microbiological recurrence of the same organism and/or all-cause mortality within 30 days of discontinuation. Results: Overall, 95 CLABSIs were included. Of 92 patients, 46 (50%) were immunocompromised. For patients with catheters removed prior to the end of therapy (n=48), the median duration of effective therapy was 13.5 days (IQR: 8.75-16 days). For patients who retained catheters throughout treatment (n=47), the median duration of effective therapy was 13 days (IQR: 9-15 days). Of these 95 CLABSIs, one patient (retained catheter) had microbiological recurrence within 30 days. Seven patients died (without microbiological recurrence), with range of duration of therapy of 6-14 days. Conclusion: There was a wide variation in length of therapy for CLABSIs caused by GNB in children. Microbiological recurrence was rare, and mortality was unrelated to microbiological recurrence. Future studies should evaluate standardization of shorter duration therapy to avoid unnecessarily prolonged antibiotic exposure. Disclosures: Sameer Patel, MD MPH, Merck (Grant/Research Support)Nexogen (Consultant)